“ZIRADOSHLAR OILASI” MAVZUSINI O’QITISHDA MAHALLIY MATERIALLARDAN FOYDALANISH (Conference Zone, 2022)
In the field of botany, it is important to use local materials to connect the theoretical knowledge of students with practice. family members were used as local material in the teaching of botany.